2020
DOI: 10.3325/cmj.2020.61.230
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone levels are associated with metabolic components: a cross-sectional study

Abstract: Aim To analyze the association of thyroid function and hormone levels with metabolic syndrome (MetS) and its components. Methods This cross-sectional population-based study involved 2183 Croatian individuals with no history of thyroid disease, hypertension, diabetes, and hyperlipidemia. MetS was diagnosed according to the National Cholesterol Education Program’s Adult Treatment Panel III criteria. Results We found no association between thyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
1
0
1
Order By: Relevance
“…The absence of significant differences in TSH concentrations in subsequent BMI ranges in healthy young women does not support the common opinion of a direct association between hypothyroidism and obesity or between hyperthyroidism and weight loss 3 . However, the results can demonstrate local involvement of fT3 and fT3/fT4 ratio in the regulation of body weight and confirm another opinion that changes in the serum concentrations of these hormones may be a consequence rather than the cause of changes in the body weight 10 , 35 . Free triodothyronine (fT3) is the active form, converted from free thyroxine (fT4) in peripheral tissues, and the degree of conversion is reflected in the fT3/fT4 ratio.…”
Section: Discussionsupporting
confidence: 78%
“…The absence of significant differences in TSH concentrations in subsequent BMI ranges in healthy young women does not support the common opinion of a direct association between hypothyroidism and obesity or between hyperthyroidism and weight loss 3 . However, the results can demonstrate local involvement of fT3 and fT3/fT4 ratio in the regulation of body weight and confirm another opinion that changes in the serum concentrations of these hormones may be a consequence rather than the cause of changes in the body weight 10 , 35 . Free triodothyronine (fT3) is the active form, converted from free thyroxine (fT4) in peripheral tissues, and the degree of conversion is reflected in the fT3/fT4 ratio.…”
Section: Discussionsupporting
confidence: 78%
“…A recent study found a signi cant positive association between TSH and Homeostatic Model Assessment of insulin resistance [22]. On the other hand, a recent systematic review found no association between subclinical hypothyroidism and incident diabetes [23]. It should be noted that in spite of not reaching a diabetic level, HbA1c was signi cantly higher among patients with subclinical hypothyroidism in our sample.…”
Section: Discussioncontrasting
confidence: 60%